Feasibility of renewable energy microgrids with vehicle-to-grid technology for smart villages: A case study from India - Lalith Pankaj Raj Nadimuthu; Kirubakaran Victor; Mohit Bajaj; Milkias Berhanu Tuka (Results in Engineering)
The socioeconomic development of a nation is inextricably linked to the availability of electricity. A significant portion of the worldwide inhabitants, specifically 840 million people, still lacks access to electricity, as per the World Sustainable Energy Goals Report. The Integrated Rural Energy Planning program aims to provide environmentally sound energy planning for domestic utilization. This paper adopts the 100 % household survey methodology for primary data collection for estimating energy potential and energy utilization patterns in the alamarathupatti village of Dindigul district, Tamil Nadu. The survey comprises the systematic questioner to obtain the accurate primary data of the hamlet. Based on the survey, hamlet-wise peak power demand was identified. Therefore, systematic energy planning is formulated for peak shaving by incorporating renewable energy generations with energy storage system. This paper elaborates on the proposed renewable integrated smart Micro (or) nano grid for peak shaving of the power grid. The primary source of the smart microgrid is solar photovoltaic-powered vehicle-to-grid (V2 G) energy storage technology and biomass energy conversion. Biogas generation through anaerobic digestion and producer gas generation through gasification meet the village's commercial electrical energy demand through a dual-fed generator set coupled with a smart microgrid to enhance the rural farmer's livelihood. Solar photovoltaic-powered V2 G shares 75 %, and biomass energy conversion shares 25 % of peak demand for effective peak shaving by the proposed smart microgrid. Therefore, proper rural energy planning with the renewable integrated microgrid system could enhance livelihood and leading to its economic development in an environmentally sustainable manner.